"Putting your house in order" - an exploration of the idea of a good death among people dying in mid-life - Charlton, Diana Eleanor Marjorie (My University, 2006)
This qualitative study set out to explore the idea of a good death through in-depth interviews with six terminally ill patients with cancer aged between thirty-seven and fifty-two, in other words in mid-life. Thematic content analysis was used to examine overt and covert themes revealed in semi-structured interviews that had been transcribed verbatim. Significant fear of dying was revealed and although respondents did not seem to have a conscious idea of a good death, they had a clear concept of good dying. Two key components of good dying were not being in pain or distress from physical symptoms, and wanting to drift off into a final “sleep” rather than being fully alert until the end. It was noticeable that, whether or not patients had religious convictions, relatively little attention appeared to be paid directly to what might or might not follow the moment of death itself, for example an afterlife. Preparation for good dying included completing a will, sorting out financial affairs and, for some patients, planning a funeral. At times this preparation also included trying to mend conflicted relationships and make plans for the ongoing care of family members. It is postulated that these preparations helped re-constitute a sense of order that had been shattered by the chaos of being declared terminally ill at a time of life when this was non-normative. Moreover, taking care of practical needs re-established a sense of agency, helped achieve some sense of closure and symbolised a measure of acceptance of their dying status. Respondents did not seem to experience external pressure from others to die in a certain way, although two people were particularly aware of their influence on how others in the family felt and thus tended to pretend to feel better than they did.
Student Number : 7916069 - MA research report - School of Human and Community Development - Faculty of Humanities
Keywords: good death; terminally ill patients; mid-life; fear of dying; pain or distress; drift off into a final “sleep”